Game Theoretical-Based Logistics Costs Analysis: A Review - Husni Teja Sukmana; Andree Emmanuel Widjaja; Hery Juan Situmorang (International Transactions on Artificial Intelligence, 2022)
As the range and complexity of outsourced services for logistics increase, Logistics has evolved into a distinct commercial service. The question of how to fairly charge logistics services has grown urgent. In this study, we conduct a comprehensive evaluation of the academic research on the cost of logistics services employing bibliometric and analyzing the content methodologies, with a focus on the application of game theory. Using three criteria logistics situations, game models, and influencing factors, we contrast and evaluate the research. This research examines the important stakeholders and research situations in logistics pricing examine the most suitable and often utilized game models, as well as highlights the primary elements determining logistics pricing. To close the gaps in our current understanding, we offer potential study directions. The present level of evidence-based study in the area of price for logistics is thoroughly reviewed in this work, this contributes to the creation of new models. From a pricing perspective, the results of this investigation are helpful in the advancement of logistics services, as a result, logistical activities will be more economical as well as environmentally sustainable.